Efficacy and safety of PCSK9 inhibitors in patients with chronic kidney disease - Haixia Tang; Xiaomin Li; Fengmei Wang; Hong Liu; Xiaoliang Zhang; Bicheng Liu; Bin Wang (BMC Nephrology)
Abstract Background This study aimed to assess the efficacy and safety of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors in lowering lipid levels among chronic kidney disease (CKD) patients, including those with stages 4–5 CKD. Methods CKD patients with atherosclerotic cardiovascular disease treated between January 2022 and December 2022 at Zhong Da Hospital affiliated with Southeast University were enrolled in this study. Patients received either evolocumab or alirocumab for three months, either in combination with statin therapy with or without ezetimibe. Efficacy and safety measures were compared among the different groups before and after treatment. Results A total of 496 CKD patients were included in the study, comprising 263 with stages 1–2 CKD, 170 with stage 3 CKD, and 63 with stages 4–5 CKD. Among them, 301 patients were classified into the atherosclerotic cardiovascular disease (ASCVD) group, whereas 195 were classified into the very-high-risk ASCVD group. LDL-C, total cholesterol (TC), and lipoprotein (a) (Lp(a)) levels decreased significantly in all groups, including stages 4–5 CKD patients, after treatment (P < 0.05). The serum creatinine (Scr) level and estimated glomerular filtration rate (eGFR) remained stable during treatment (P > 0.05). The incidence of adverse drug events did not differ significantly among the different kidney function groups (P ≥ 0.05). Conclusions PCSK9 inhibitors can be effectively and safely utilized for lipid-lowering therapy in CKD patients, even those with stages 4–5 CKD. Clinical trial number Not applicable.